Anomalous plasticity of body-centered-cubic crystals with non-Schmid effect. (15th May 2018) - Cho, Hansohl; Bronkhorst, Curt A.; Mourad, Hashem M.; Mayeur, Jason R.; Luscher, D.J.
Abstract: Plastic deformations in body-centered-cubic (bcc) crystals have been of critical importance in diverse engineering and manufacturing contexts across length scales. Numerous experiments and atomistic simulations on bcc crystals reveal that classical crystal plasticity models with the Schmid law are not adequate to account for abnormal plastic deformations often found in these crystals. In this paper, we address a continuum mechanical treatment of anomalous plasticity in bcc crystals exhibiting non-Schmid effects, inspired from atomistic simulations recently reported. Specifically, anomalous features of plastic flows are addressed in conjunction with a crystal plasticity model involving two non-Schmid projection tensors widely accepted for representing non-glide components of an applied stress tensor. Further, modeling results on a representative bcc tantalum are presented and compared to experimental data at a range of low temperatures to provide physical insight into deformation mechanisms in these crystals with non-Schmid effects.